Ancient Rome - Bell, Samantha (Civilizations of the world (Focus Readers (Firm)), 2020)
Explores the rise and fall of ancient Rome, focusing on its government, the daily lives of its citizens, and its contributions to life today. Includes color photographs and illustrations, critical thinking questions, a glossary, and further resources.